Twelve-month outcomes of a community-based, father-daughter physical activity program delivered by trained facilitators - Lee M. Ashton; Anna T. Rayward; Emma R. Pollock; Stevie-Lee Kennedy; Myles D. Young; Narelle Eather; Alyce T. Barnes; Daniel R. Lee; Philip J. Morgan (BMC, 2024)
Abstract Background Dads and Daughters Exercising and Empowered (DADEE) is a program targeting fathers/father-figures to improve their daughters' physical activity and well-being. Previous randomised controlled efficacy and effectiveness trials of DADEE demonstrated meaningful improvements in a range of holistic outcomes for both fathers and daughters in the short-term. This study aims to assess the long-term impact (12-months) of the program when delivered in the community by trained facilitators. Methods Fathers/father-figures and their primary school-aged daughters were recruited from Newcastle, Australia into a single-arm, non-randomised, pre-post study with assessments at baseline, 10-weeks (post-intervention) and 12-months. The 9-session program included weekly 90-min educational and practical sessions, plus home-based tasks. The primary outcome was fathers' and daughters' days per week meeting national physical activity recommendations (≥ 30 min/day of MVPA for fathers, ≥ 60 min/day MVPA for daughters). Secondary outcomes included physical activity, screen time, self-esteem, father-daughter relationship, social-emotional well-being, parenting measures, and process outcomes (including recruitment, attendance, retention and program acceptability). Results Twelve programs were delivered with 257 fathers (40.0 ± 9.2 years) and 285 daughters (7.7 ± 1.9 years). Mixed effects regression models revealed significant intervention effects for the primary outcome, with fathers increasing the days/week meeting physical activity recommendations by 27% at 10-weeks (p < 0.001) and by 19% at 12-months (p < 0.001) compared with baseline. Likewise, for daughters there was a significant increase by 25% at 10-weeks (p < 0.001) and by 14% at 12-months (p = 0.02) when compared to baseline. After conducting a sensitivity analysis with participants unaffected by COVID-19 lockdowns (n = 175 fathers, n = 192 daughters), the primary outcome results strengthened at both time-points for fathers and at 12-months for daughters. Additionally, the sensitivity analysis revealed significant intervention effects at post-program and 12-months for all secondary outcomes in both fathers and daughters. Furthermore, the process outcomes for recruitment capability, attendance, retention and satisfaction levels were high. Conclusions Findings provide support for a sustained effect of the DADEE program while delivered in a community setting by trained facilitators. Further investigation is required to identify optimised implementation processes and contextual factors to deliver the program at scale. Trial registration ACTRN12617001450303 . Date registered: 12/10/2017.